Effectiveness of ABCN Interventions on Reducing Under Two Child Malnutrition in a Selected NNP Area (Bangladesh Journal of Nutrition, 2013)
This cross-sectional comparative study was conducted in Muradnagar Upazila, Comilla district to see the effectiveness of NNP-ABCN (Area Based Community Nutrition) interventions on reducing under-two child malnutrition (0-23 months) and establish whether there is any significant difference from the non-operational area. A total of 240 households, of which 120 were from the NNP project area with children aged between 0-23 months were randomly selected. In households with more than one child at this age category, the last child was selected. Indices of nutritional status that is weight-for-age, length-for-age and weight-for-length were computed for the measurement of nutritional status. Analysis of nutritional status data show that the prevalence of underweight (